Comparison of direct and indirect alcohol markers with PEth in blood and urine in alcohol dependent inpatients during detoxication - Winkler, Michaela; Skopp, Gisela; Alt, A.; Miltner, E.; Jochum, Th.; Daenhardt, C.; Sporkert, F.; Gnann, H.; Weinmann, W.; Thierauf, A. (International journal of legal medicine, 2013)
The importance of direct and indirect alcohol markers to evaluate alcohol consumption in clinical and forensic settings is increasingly recognized. While some markers are used to prove abstinence from ethanol, other markers are suitable for detection of alcohol misuse. Phosphatidyl ethanol (PEth) is ranked among the latter. There is only little information about the correlation between PEth and other currently used markers (ethyl glucuronide, ethyl sulfate, carbohydrate deficient transferrin, gamma-glutamyl transpeptidase, and methanol) and about their decline during detoxification. To get more information, 18 alcohol-dependent patients in withdrawal therapy were monitored for these parameters in blood and urine for up to 19 days. There was no correlation between the different markers. PEth showed a rapid decrease at the beginning of the intervention, a slow decline after the first few days, and could still be detected after 19 days of abstinence from ethanol.